Public and Private Lives: Institutional Structures and Personal Supports in Low-Income Single Mothers’ Educational Pursuits - Cerven, Christine (Education Policy Analysis Archives, 2013)
Drawing on a case study of 60 low-income single mothers in California, I present a grounded account of the barriers and supports single mothers encounter in their pursuit of postsecondary education (PSE) and detail what the women themselves attributed to their success. I highlight the role both significant others (peers, family, friends) and institutional structures (the county welfare department and a community college district) played in their access and persistence within a community college district. In doing so, I provide a rich portrait of single mothers’ pursuits of postsecondary education to inform the empirical research gaps in the literature on the effects of welfare reform on the pursuit of PSE. I find that not only does the support of significant others play an important role in single mothers’ access of PSE, but that referrals to PSE from the county welfare department were as equally important—a finding that counters the dominant discussion in scholarly work on the barriers welfare departments pose to welfare recipients’ pursuit of PSE. Supportive significant others remained an important factor in the women’s abilities to persist in their postsecondary pursuits, but the women also cited student support programs designed to address the needs of low-income students as facilitating their persistence. The implications for the impact of welfare department practices, community college support structures and close networks of significant others on low-income single mothers’ access and persistence in a community college district are discussed.